Answers

  • Brainly User
2016-06-03T11:20:47+08:00
1) an = 2n - 1
    a₁ = 2(1) - 1
    a₁ = 1
   
    a₂ = 2(2) - 1
    a₂ = 4 - 1
    a₂ = 3
   
    The difference between a₂ and a₁ is 2 (that is, 3-1).  Therefore, the first five terms are.  1, 3, 5, 7, 9.

2)  an = 12 - 3n
     a₁ = 12 - 3(1) 
     a₁ = 12 - 3
     a₁ = 9
  
     a₂ = 12 - 3(2)
     a₂ = 12 - 6
     a₂ = 6
  
The difference between a₂ and a₁ is -3 (that is, 6 - 9).  Therefore, the first five terms are:  9, 6, 3, 0, -3.

3)  an = 3n
     a₁ = 3(1)
     a₁ = 3
 
     a₂ = 3(2)
     a₂ = 6

The difference between a₁ and a₂ is 3 (that is, 6 - 3).  Therefore, the first five terms are 3, 6, 9, 12, 15

4) an = -2n
    a₁ = -2 (1)
    a₁ = -2
  
    a₂ = -2(2)
    a₂ = -4
    
The difference between a₁ and a₂ is -2 (that is, -4 - -2 or -4 + 2).  Therefore, the first five terms are -2, -4, -6, -8, -10.




3 5 3